Geography at the Cuba University: achievements, difficulties and challenges of teaching in science committed to the economic and social development of a society in transformation - González Sousa, Roberto; Lazo Machado, Andrés; Pérez Rodríguez, Nancy (Anales de Geografía de la Universidad Complutense, 2009)
Sin resumen